2022
DOI: 10.3389/fnagi.2021.746236
|View full text |Cite
|
Sign up to set email alerts
|

The “Neural Shift” of Sleep Quality and Cognitive Aging: A Resting-State MEG Study of Transient Neural Dynamics

Abstract: Sleep quality changes dramatically from young to old age, but its effects on brain dynamics and cognitive functions are not yet fully understood. We tested the hypothesis that a shift in brain networks dynamics relates to sleep quality and cognitive performance across the lifespan. Network dynamics were assessed using Hidden Markov Models (HMMs) in resting-state MEG data from a large cohort of population-based adults (N = 564, aged 18–88). Using multivariate analyses of brain-sleep profiles and brain-cognition… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 79 publications
1
6
0
Order By: Relevance
“…Functional or effective connectivity measured by fMRI has provided essential information on the functional organization of the human brain network. Age‐related changes in functional connectivity have been extensively examined in resting‐state fMRI studies (Andrews‐Hanna et al, 2007 ; Chan et al, 2014 ; Ferreira & Busatto, 2013 ; Geerligs et al, 2015 ; Grady, 2008 ; Grady et al, 2016 ; Masuda et al, 2018 ; Tibon et al, 2021 ; Tibon & Tsvetanov, 2021 ). However, functional connectivity estimated by fMRI involves methodological issues, such as vascular reactivity and head motion, which may change with diseases or age (Geerligs et al, 2017 ; Lehmann et al, 2017 ; Tsvetanov et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Functional or effective connectivity measured by fMRI has provided essential information on the functional organization of the human brain network. Age‐related changes in functional connectivity have been extensively examined in resting‐state fMRI studies (Andrews‐Hanna et al, 2007 ; Chan et al, 2014 ; Ferreira & Busatto, 2013 ; Geerligs et al, 2015 ; Grady, 2008 ; Grady et al, 2016 ; Masuda et al, 2018 ; Tibon et al, 2021 ; Tibon & Tsvetanov, 2021 ). However, functional connectivity estimated by fMRI involves methodological issues, such as vascular reactivity and head motion, which may change with diseases or age (Geerligs et al, 2017 ; Lehmann et al, 2017 ; Tsvetanov et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“… 16 Thus, there is no consensus regarding whether aging involves multi-frequency dynamic oscillatory changes or is characterized by dominant alpha frequency deficiency. Previous Cam-CAN studies 17-20 have indicated reduced neural efficiency or specificity rather than compensation across lifespan. For example, Tibon et al 17 , 18 showed that there was an age-related ‘neural shift’ with decreased occurrence of ‘lower-order’ networks in early visual states and increased occurrence of ‘higher-order’ fronto-temporal-parietal networks in visual and sensorimotor states.…”
Section: Introductionmentioning
confidence: 92%
“…Previous Cam-CAN studies 17-20 have indicated reduced neural efficiency or specificity rather than compensation across lifespan. For example, Tibon et al 17 , 18 showed that there was an age-related ‘neural shift’ with decreased occurrence of ‘lower-order’ networks in early visual states and increased occurrence of ‘higher-order’ fronto-temporal-parietal networks in visual and sensorimotor states. Another leading theory, 19 , 20 the posterior-to-anterior shift in aging (PASA), states that the anterior regions are recruited when posterior cortical function is impaired.…”
Section: Introductionmentioning
confidence: 92%
“…Structure coefficients can be viewed as "loadings", indicating to what degree each variable contributes to the predictions made by the model. These coefficients can be used to guide interpretation and are particularly useful in the presence of multicollinearity (Sherry and Henson, 2005;Tibon et al, 2021;Tibon and Tsvetanov, 2022). Therefore, we used the computed structure coefficients for two main purposes, as detailed below: (1) to investigate the correspondence between the two datasets, and (2) to identify brain regions in which FD most reliably predicts group attribution.…”
Section: General Linear Model and Structure Coefficientsmentioning
confidence: 99%